Structure and Phase Composition of Heat-Resistant Ni–Al–Co Alloy After Annealing and Creep; Russian Physics Journal; Vol. 61, iss. 12 - Koneva N. A. Nina Aleksandrovna; Potekaev A. I. Aleksandr Ivanovich; Nikonenko E. L. Elena Leonidovna; Popova N. A. Nataljya Anatoljevna; Klopotov A. A. Anatoly Anatoljevich; Klopotov V. D. Vladimir Dmitrievich (2019, 2019)
Title screen